Statistical analysis for mechanical properties of polypropylene fiber reinforced lightweight concrete containing silica fume exposed to high temperature - Tanyildizi, Harun (Elsevier Sci Ltd, 2009)
In this study, the effect of polypropylene fiber and silica fume on the mechanical properties of light weight concrete exposed to high temperature was investigated experimentally and statistically. The mixes containing silica fumes (0% and 10%) and polypropylene fibers (0%, 0.5%, 1% and 2%) were prepared. The compressive and flexural strength of lightweight concrete samples were determined after being exposed to high temperatures (400, 600 and 800 degrees C). Three control factors (silica fume percentage, polypropylene fiber percentage and high temperature degree) were used for this study. The Taguchi method was used to determine the optimum conditions and to reduce the numbers of experiments. The level of importance of the experimental parameters on the mechanical properties of lightweight concrete was determined by using variance (Anova) method. The results showed that the most effective parameters on the mechanical properties of lightweight concrete were found as heating degree. Furthermore, the optimum parameters of compressive strength were different from flexural strength. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: High-Performance Concrete; Residual Strength; Pore Structure; Fire; Optimization; Resistance; Aggregate; Behavior; Design; Hpc